2011
DOI: 10.1617/s11527-011-9756-3
|View full text |Cite
|
Sign up to set email alerts
|

Mixture optimization of cement treated demolition waste with recycled masonry and concrete

Abstract: Due to environmental reasons and the shortage of natural resources, it is greatly valuable to recycle construction and demolition waste (CDW) as much as possible. One of effective ways to reuse more CDW is to produce a cemented road base material. The recycled CDW however is a mix of recycled masonry and concrete with a wide variation in composition. This implies that the mechanical properties of cement treated demolition waste are not only determined by cement content and degree of compaction, but also by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…Due to social recognition on the quality issue as well as the quality degradation in application to concrete products, studies have been experimental rather than leading to field application. Furthermore, most studies have been conducted on waste concrete, for example, recycled aggregate and waste concrete fine powder, while further studies are required on construction materials that recycle various construction wastes [22][23][24][25][26][27][28]. shows the yearly waste generation, which was based on statistical data from "A Current Status of National Waste Generation and Treatment" provided by the South Korean Ministry of Environment [29].…”
Section: Types and Trends Of Construction Wastesmentioning
confidence: 99%
“…Due to social recognition on the quality issue as well as the quality degradation in application to concrete products, studies have been experimental rather than leading to field application. Furthermore, most studies have been conducted on waste concrete, for example, recycled aggregate and waste concrete fine powder, while further studies are required on construction materials that recycle various construction wastes [22][23][24][25][26][27][28]. shows the yearly waste generation, which was based on statistical data from "A Current Status of National Waste Generation and Treatment" provided by the South Korean Ministry of Environment [29].…”
Section: Types and Trends Of Construction Wastesmentioning
confidence: 99%
“…These studies have demonstrated the possibility of recycling construction waste as a substitute for new materials. Chinese researchers have mainly focused on recycled aggregate concrete and nearly all aspects of mechanical properties and structural performances have been covered [14][15][16]. Xiao et al [16] reviewed and summarized all of those achievements by Chinese researchers and provided the basis for the further study of recycled concrete.…”
Section: Concrete Recycling Researchmentioning
confidence: 99%
“…Xuan ve diğ. (2012) yaptığı bir çalışmada, çevresel nedenler ve doğal kaynakları korumak için inşaat yıkıntı atıklarının mümkün olduğunca geri dönüştürülmesi ve değerlendirilmesinin ülkelerin ekonomisine ciddi katkılar sağlayacağını vurgulamışlardır [18]. Bu sebeple, killerin mühendislik özelliklerini iyileştirmesi üzerine çeşitli çalışmalar yapılmıştır.…”
Section: Introductionunclassified